2020
DOI: 10.1177/0022034520915877
|View full text |Cite
|
Sign up to set email alerts
|

GPR39 Overexpression in OSCC Promotes YAP-Sustained Malignant Progression

Abstract: The clinical outcome of oral squamous cell carcinoma (OSCC) has not improved in recent years, mainly due to the limited effective targeted therapy that has been applied. Recently, a transcriptional coactivator, YAP, has been shown to have a key regulatory role in malignant progression in multiple cancers, including OSCC. But pharmacologically targeting YAP or the Hippo pathway, which is the main signaling pathway regulating YAP, has been proven to be challenging. Therefore, uncovering YAP upstream reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 39 publications
0
27
0
Order By: Relevance
“…GPR39 plays an important role in wound healing, depression, inflammatory bowel diseases, alcohol use disorder, insulin secretion and several cancers [ 23 , 46 , 48 52 ]. However, the neuroprotective function of GPR39 has been partially confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…GPR39 plays an important role in wound healing, depression, inflammatory bowel diseases, alcohol use disorder, insulin secretion and several cancers [ 23 , 46 , 48 52 ]. However, the neuroprotective function of GPR39 has been partially confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…GPR39 plays an important role in wound healing, depression, in ammatory bowel diseases, alcohol use disorder, insulin secretion and several cancers [23,46,[48][49][50][51][52]. However, the neuroprotective function of GPR39 has been partially con rmed.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of GPR39 and related subsequent signaling cascade has been identi ed in several cells and shown to regulate a vast array of physiological functions, such as proliferation, differentiation, ion transport and tight junction formation [16]. Moreover, activation of GPR39 has been demonstrated to promote wound healing, ameliorate symptoms of in ammatory bowel diseases, dampen epileptic seizure activity, reduce anxietylike behaviors and regulate insulin secretion and malignant progression of several cancers [17][18][19][20][21][22][23][24]. Recently, accumulating in vitro evidence demonstrated that GPR39 exhibits anti-in ammatory activity by reducing the expression of pro-in ammatory cytokines(IL-1β IL-6), enhancing anti-in ammatory cytokines production (IL-10), ameliorating oxidative stress and mitochondrial dysfunction [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…GPR39 has been reported to regulate gastrointestinal motility and secretion, food intake, insulin secretion, tissue repair, apoptosis and synaptic transmission [20], mediating intracellular signaling pathways [21]. Coincidentally, the dysregulation and involvement of GPR39 in the development and progression of cancer have been also observed [22][23][24][25][26]. Here we strove to find additional modes of HBV proliferation through the properties of GPR39, also investigating novel features of the receptor through HBV replication machinery.…”
Section: Introductionmentioning
confidence: 96%